(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction and objectives: Transurethral resection of the prostate (TURP) was still considered as the gold standard in treatment to improve lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH). The aim of this study was to investigate the effect of TURP on sexual function in patients with BPH between 2022 and 2023. Subjects and methods: A total of 79 patients who underwent TURP were retrospectively assessed. All patients were evaluated for sexual function at baseline and 6 months after TURP by using IIEF- 15, IIEF-5, PEDT. Results: 100% of patients had sexual activity before and after TURP. Before surgery, 44% of patients had good erections, this rate decreased after surgery to 38%. In the group of patients with erectile dysfunction before surgery, there was an improvement in erection ability (IIEF-5 score increased from 11.37 ± 2.34 to 15.13 ± 2.15). PEDT and IIEF-15 scores showed no change in symptoms of premature ejaculation and sexual dysfunction after surgery. Conclusions: The results comfirmed that TURP do not wreak a havoc on sexual function, and patients with preexisting erectile function were improved after TURP.